DOES INDONESIAN HOUSEHOLD SAVING HAS CYCLE? - Ferry Hadiyanto (Indonesian Journal of Economics and Business, 2011)
Household saving is how much of income is set aside after it is consumed. This type of saving is one of important aspect of household behavior, especially for developing countries. Many empirical studies had addressed to explore and to test the pattern of household saving. Initiated by Modigliani and Ando (1963) who proposed the hump shape of life cycle of saving then this hypothesis grows even wider and deeper. Considering the foregoing, it is therefore very important  for policy maker to know and to analized whether low or high the household saving rate in the country. Browning and Lusardi (1996) provides a good comprehensive review of the recent household saving literatures. Deaton (1991) finds that saving will be a back up stock of income to maintain concumption during bad times, even if there is liquidity constraint or imperfect capital market.  Also Horioka (1997) found that the age structure of population affects household saving rate in japan and strong support for the life cycle model. Similar to this is also tested for the United State household that working age of household head had a negative and sgnificant impact on personal saving Gale, Sabelhaus and Hall (1991) (Thornton, 2001). Other literatures that tries to examine and comparing between countries whether saving is affected by income growth is by Paxson (1995) and Deaton and Paxson (2000) for four cross-countries and looks an evidence of household saving in Latin America and South East Asia Counties was tested by Attanasio and Szekely (2000). They found that household saving follow the life cycle model, eventhough for some countries which has a volatile economic growth, show a weak evidence. Modigliani and Ando (1963) started to improve what proposed by Modigliani and Brumberg (1954) with the view that the behavior of the life cycle savings will reach a peak at the productive age and decreased continuously in ages up to retirement as an impact of consumption smoothing behavior. Because of a little evidences have been done exploring and testing this research topic for the Indonesia household behavior, therefore  this papers address to test using Longitudinal data of Indonesia Family Life Survey (IFLS) of year 1993, 2000 and 2007. This paper analyze the important influence of age and cohort effect to the behavior of household which went through the period of such good and bad in the Indonesia economy.